Anaerobic fermentation of hybrid Pennisetum mixed with fruit and vegetable wastes to produce volatile fatty acids. Issue 55 (9th September 2020) - Xing, Tao; Yu, Shutai; Zhen, Feng; Kong, Xiaoying; Sun, Yongming
Abstract : pH and co-digestion conditions were applied for optimal VFA production from hybrid Pennisetum (HP) and fruit and vegetable waste (FVW). Abstract : The production of volatile fatty acids (VFAs) via anaerobic fermentation is a new technology that provides a high-value utilization of biomass. This work used hybrid Pennisetum (HP) and fruit and vegetable waste (FVW) as raw materials to investigate the influence of different ratios of HP to FVW on the production of VFAs under different methanogenic inhibition conditions. It has been shown that both alkaline and neutral conditions (using methanogenic inhibitors), could generate higher acid yields than acidic conditions. Under initial alkaline conditions, mono-fermentation of HP and FVW could obtain maximum VFA yields of 596 ± 22 mg g −1 VS and 626 ± 7 mg g −1 VS, which were higher than those obtained under neutral conditions. In contrast, there was no remarkable difference in VFA yield between alkaline and neutral conditions when co-fermentation of HP and FVW was carried out. The VFA yields decreased significantly with the process of co-fermentation. The maximum VFA yields were decreased by 33.2% and 21.9% when HP was fermented with 15% and 30% of FVW, respectively. There was a clear difference in the composition of VFAs obtained under different initial conditions. The maximum selectivity was achieved under alkaline conditions, where the acetate content reached more than 85%. This study brings a theoretical basis for optimizing the anaerobic fermentation process of lignocellulose to produce VFAs.